Opposite Regulatory Effects of Immobilized Cations on the Folding Vs. Assembly of Melittin - Yu, Lanlan; Deng, Zhun; Zhang, Wenbo; Liu, Shuli; Zhang, Feiyi; Zhou, Jianjian; Ma, Chunhua; Wang, Chenxuan (Frontiers in Chemistry, 2021)
Ions are crucial in modulating the protein structure. For the free ions in bulk solution, ammonium is kosmotropic (structure forming) and guanidinium is chaotropic (structure breaking) to the protein structure within the Hofmeister series. However, the effect of immobilized ions on a protein surface is less explored. Herein, we explored the influence of two immobilized cations (ammonium in the side chain of lysine and guanidinium in the side chain of arginine) on the folding and assembly of melittin. Melittin adopts an α-helix structure and is driven by hydrophobic interactions to associate into a helical bundle. To test the influence of immobilized cations on the peptide structure, we designed the homozygous mutants exclusively containing ammonium (melittin-K) or guanidinium (melittin-R) and compared the differences of melittin-K vs. melittin-R in their folding, assembly, and molecular functions. The side chains of lysine and arginine differ in their influences on the folding and assembly of melittin. Specifically, the side chain of R increases the α-helical propensity of melittin relative to that of K, following an inverse Hofmeister series. In contrast, the side chain of K favors the assembly of melittin relative to the side chain of R in line with a direct Hofmeister series. The opposite regulatory effects of immobilized cations on the folding and assembly of melittin highlight the complexity of the noncovalent interactions that govern protein intermolecular architecture.